HUBUNGAN DISIPLIN BELAJAR DENGAN HASIL BELAJAR SOSIOLOGI SISWA KELAS XI IPS SMA N 3 SIJUNJUNG TAHUN AJARAN 2012 / 2013 KABUPATEN SIJUNJUNG - Ardira, Vony; Melia, Yenni; Erningsih, Erningsih (Pendidikan Sosiologi, 2013)
This research is classified as quantitative research with ex post facto type and correlational research type. Questionnaire is used as technique of data colletion and correlation product moment is used as technique of data analysis. The population of this research is all XI IPS classes in SMA N 3 Sijunjung which is registered in 2012/2013 academic year where total of students is 65 students and researcher uses porpotional random sampling as sampling technique with total sample is 56 students. Research findings showed that there is a correlation between students learning discipline in sosiology which consists of two indicators: 1). Obey the regulation in learning process, and 2). Be responsible in doing task or examination, where rhitung >rtabel so H0 rejected Ha accepted. According to this finding, learning discipline is rhitung = 0,676 > rtabel = 0,266 with significant thitung = 6,674 > ttabel = 2,000. It can be concluded that students learning discipline achievement. So, students need to improve or encourage good learning discipline and it will give positive impact or effect t their achievement in learning.